EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KETERAMPILAN BERPIKIR KREATIF, LITERASI DIGITAL DAN HASIL BELAJAR MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR - Al Hikma Sake; Anas Arfandi; Darmawang (UNM Journal of Technology and Vocational, 2024)
This study aims to determine: (1) The Effectiveness of the Application of the Flipped Classroom Learning Model on Student Creative Thinking Skills, (2) The Effectiveness of the Application of the Flipped Classroom Learning Model on Student Digital Literacy Skills, (3) The Effectiveness of the Application of the Flipped Classroom Learning Model on Student Learning Outcomes of the Accounting Department of Alauddin Makassar State Islamic University. This research is a type of quantitative research with a quasi experimental approach. The population in this study were students of classes A, B and C of the Accounting Department at Alauddin Makassar State Islamic University totalling 92 students. The research sample amounted to 61 students. The results of this study showed: (1) The implementation of the Lantern-based flipped classroom model is effective on students' creative thinking skills, (2) The implementation of the Lantern-based flipped classroom model is effective on students' digital literacy skills. (3) The implementation of the Lantern-based flipped classroom model is effective on student learning outcomes of the Accounting Department of Alauddin Makassar State Islamic University.